From Palestine to Turtle Island: Essays on TransIndigenous Literatures - Ababneh, Mahmoud (Graduate Studies, 2025)
This manuscript dissertation/thesis explores the relationships between Turtle Island and Palestine, contributing to larger discussions in TransIndigenous studies, global Indigenous studies, and within comparative literary studies fields broadly. From Palestine to Turtle Island: Essays on TransIndigenous Literatures creates a dialogue between Indigenous arts and aesthetics centring Indigenous ways of knowing across nations, specifically on Turtle Island and in Palestine, wherein engaging with narrating history and centring Indigenous voices beyond national and exceptionalist narratives about the U.S., Israel, and Canada as colonial states. While I trace possibilities emancipating from juxtaposing Indigenous histories, I pave the way to question our current moment as an extension of settler colonial structures. This manuscript investigates how writers and artists such as Steven Salaita, Armand Garnet Ruffo, James Welch, Aicha Yassin, Charolette DeClue, and Susan Abulhawa reclaim Indigenous voices and histories, reminding readers that settler colonialism is not a past event. They also present Indigenous stories that are past, present, and futurity, surviving despite settler structures of erasure and silence. Additionally, this dissertation aims to situate Palestinian literary and cultural productions in dialogue with Anishinaabe, Cheyenne, and other productions of Algonquin Indigenous artists of Turtle Island. I examine the productive possibilities of this cross-cultural communication to uncover how Indigenous works challenge dominant narratives and offer pathways for resistance, resilience, and healing.